2017
DOI: 10.1097/wad.0000000000000169
|View full text |Cite
|
Sign up to set email alerts
|

Repressive Coping Does Not Contribute to Anosognosia in First-Diagnosis Patients With Alzheimer Disease

Abstract: Anosognosia is common in patients with Alzheimer disease (AD) even in early stages. Although neural correlates and the impact of cognitive dysfunctions have been described, possible psychodynamic processes such as a repressive coping style as described in other illnesses, have not been examined. Our study aimed to examine possible psychological influence factors on illness perception embracing a repressive coping style and cognitive functions in AD patients in the diagnostic process. Fifty-four subjects with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 45 publications
0
4
0
11
Order By: Relevance
“…Therefore, lack of awareness might also be due to affective dysfunction. In contrast, psychodynamic processes such as a repressive coping style were shown to contribute to lack of awareness …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, lack of awareness might also be due to affective dysfunction. In contrast, psychodynamic processes such as a repressive coping style were shown to contribute to lack of awareness …”
Section: Discussionmentioning
confidence: 95%
“…In contrast, psychodynamic processes such as a repressive coping style were shown to contribute to lack of awareness. 66 Bjørge et al 67 have also pointed to an inconsistency between the caregiver and the AD patient's perceptions of their relationship, and suggested that supporting distressed caregivers in changing their negative perspective might be helpful for them and their relationship quality.…”
Section: Evaluation Of the Sqcrcmentioning
confidence: 99%
“…It is possible that some unaware patients were experiencing anosognosia whereby they were unable or unwilling to recognize their impairments. The percentage of patients with anosognosia is highly variable in clinical populations, ranging from about 27% upwards to 80% (Turró-Garriga et al, 2016;Verhülsdonk et al, 2016). Understanding the degree to which anosognosia that can develop in neurodegenerative diseases is protective against declines in QOL for persons with AD dementia may be useful for understanding and addressing the burdens that may be placed on individuals who are cognitively typical yet diagnosed with AD dementia.…”
Section: Discussionmentioning
confidence: 99%
“…The management of the condition presents a wide range of challenges regarding the effective alleviation of the state. The existence of a similar situation is influenced by a wide range of problems attributable to the mental condition of the patient [9]. The effective management of Ann W. condition would be faced by various challenges, which are primarily influenced by her history with mental problems.…”
Section: Elucidation Of the Mechanisms Of The Conditionmentioning
confidence: 99%